2015
DOI: 10.1357/002224015815848811
|View full text |Cite
|
Sign up to set email alerts
|

Water masses and nutrient sources to the Gulf of Maine

Abstract: The Gulf of Maine, a semi-enclosed basin on the continental shelf of the northwest Atlantic Ocean, is fed by surface and deep water flows from outside the Gulf: Scotian Shelf Water from the Nova Scotian shelf that enters the Gulf at the surface, and Slope Water that enters at depth and along the bottom through the Northeast Channel. There are two types of Slope Water, Labrador Slope Water (LSW) and Warm Slope Water (WSW); it is these deep water masses that are the major source of dissolved inorganic nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 38 publications
6
125
1
Order By: Relevance
“…As discussed most recently in Townsend et al . [], one key puzzle in diagnosing variable Gulf hydrography lies in the complexity of the sea‐slope exchange within the NEC, which in a given year, or even month, can involve an inflow admixture of Atlantic slope water, Labrador slope water, Gulf Stream meanders, and Scotian Shelf water. NEC inflow and outflow is now known to be highly variable with depth [ Ramp et al ., ; Smith et al ., ] as well as across and along the NEC, making it a difficult system to monitor and evaluate.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As discussed most recently in Townsend et al . [], one key puzzle in diagnosing variable Gulf hydrography lies in the complexity of the sea‐slope exchange within the NEC, which in a given year, or even month, can involve an inflow admixture of Atlantic slope water, Labrador slope water, Gulf Stream meanders, and Scotian Shelf water. NEC inflow and outflow is now known to be highly variable with depth [ Ramp et al ., ; Smith et al ., ] as well as across and along the NEC, making it a difficult system to monitor and evaluate.…”
Section: Introductionmentioning
confidence: 94%
“…There is significant recent focus on the identification and explanation of ecological, biochemical, and physical change at seasonal to decadal time scales in the Gulf of Maine (GoM) and surrounding waters including the Nova Scotian Shelf (SS) [ Mountain , ; Pershing et al ., ; Smith et al ., ; Ji et al ., ; Townsend et al ., ]. Interest in GoM water mass variability is not new [ Bigelow , ; Fournier et al ., ; Petrie and Drinkwater , ; Loder et al ., ] with prevailing reasons being the presence of extensive marine life and active fisheries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, however, the source of nutrients that stimulates these toxic blooms is overwhelmingly dominated by the ocean end member (Townsend, 1998;Anderson et al, 2008). Most critical for this project is that there have been significant changes in recent years to the water properties and inorganic nutrient loads of the deep offshore-derived water masses in the GOM (e.g., Pettigrew et al, 2008;Rebuck, 2011;Smith et al, 2012;Townsend et al, submitted) that need to be better understood and monitored. showed that deep waters in the GOM (>100 m) have become slightly fresher and cooler since the 1970s, with lower nitrate (by~2-4 μM) but higher silicate (also bỹ 2-4 μM).…”
Section: Nutrient Dynamics Climate Change and Harmful Algal Blooms mentioning
confidence: 99%
“…Key water mass inflows influencing this marginal sea include the upstream fresh/cold Scotian Shelf and Labrador Sea currents, and the adjoining salty/warm northwestern (NW) Atlantic shelf (Mountain [1]; Townsend et al [2]; Feng et al [3]; Peterson et al [4]). The primary inflow to the GoM is through The dominance of subsurface GoM exchange pathways has, so far, limited the utility of surface remote sensing data for monitoring GoM dynamics.…”
Section: Introductionmentioning
confidence: 99%